Unveiling the microbiota of sauce-flavor Daqu and its relationships with flavors and color during maturation - Dong, Weiwei; Yu, Xiang; Wang, Luyao; Zou, Menglin; Ma, Jiyuan; Liu, Jun; Feng, Yanli; Zhao, Shumiao; Yang, Qiang; Hu, Yuanliang; Chen, Shenxi (Frontiers in Microbiology, 2024)
This study investigated the microbial community in three-color sauce-flavor Daqu (black, yellow, and white) throughout their maturation processes, together with their physicochemical factors, culturable microbes, flavor components, and fermenting vitalities. Results from highthroughput sequencing revealed distinct microbial diversity, with more pronounced variations in bacterial community than in fungal community. Firmicutes and Ascomycota emerged as the most dominant bacterial and fungal phyla, respectively, during maturation. Genus-level analysis identified Kroppenstedia, Virgibacillus, and Bacillus as dominant bacteria in black Daqu, yellow Daqu, and white Daqu, severally, while Thermoascus was shared as the core dominant fungi for these Daqu. Physicochemical factors, particularly acidity, were found to exert a significant impact on microbial community. Kroppenstedtia was the key bacteria influencing the color formation of these Daqu. Furthermore, correlations between dominant microbes and flavor compounds highlighted their role in Daqu quality. Molds (Aspergillus, Rhizomucor, and Rhizopus), excepting Bacillus, played a crucial role in the formation of pyrazine compounds. Consequently, this study offers innovative insights into the microbial perspectives on color and pyrazine formation, establishing a groundwork for future mechanized Daqu production and quality control of sauce-flavor baijiu.